The immunity priming effect of the Arabidopsis phyllosphere resident yeast Protomyces arabidopsidicola strain C29 - Wang, Kai; Auzane, Agate; Overmyer, Kirk (Frontiers in Microbiology, 2022)
The phyllosphere is a complex habitat for diverse microbial communities. Under natural conditions, multiple interactions occur between host plants and phyllosphere resident microbes, such as bacteria, oomycetes, and fungi. Our understanding of plant associated yeasts and yeast-like fungi lags behind other classes of plant-associated microbes, largely due to a lack of yeasts associated with the model plant Arabidopsis, which could be used in experimental model systems. The yeast-like fungal species Protomyces arabidopsidicola was previously isolated from the phyllosphere of healthy wild-growing Arabidopsis, identified, and characterized. Here we explore the interaction of P. arabidopsidicola with Arabidopsis and found P. arabidopsidicola strain C29 was not pathogenic on Arabidopsis, but was able to survive in its phyllosphere environment both in controlled environment chambers in the lab and under natural field conditions. Most importantly, P. arabidopsidicola exhibited an immune priming effect on Arabidopsis, which showed enhanced disease resistance when subsequently infected with the fungal pathogen Botrytis cinerea. Activation of the mitogen-activated protein kinases (MAPK), camalexin, salicylic acid, and jasmonic acid signaling pathways, but not the auxin-signaling pathway, was associated with this priming effect, as evidenced by MAPK3/MAPK6 activation and defense marker expression. These findings demonstrate Arabidopsis immune defense priming by the naturally occurring phyllosphere resident yeast species, P. arabidopsidicola, and contribute to establishing a new interaction system for probing the genetics of Arabidopsis immunity induced by resident yeast-like fungi.